SAFETY ISSUES OF EMULSION FOOD SYSTEMS WITH SUGAR GLYCERIDES - Біла, Галина; Коробка, Юлія; Антрапцева, Надія (Modern engineering and innovative technologies, 2022)
The results of determining the safety and quality ofemulsion food systems with sugar glycerides are presented and discussed. Microbiological analysis of the quality of sauces with different sugar glyceride content was performed. The presence of microorgan